Spiraea duthieana (Rosaceae), a report after a century and rank change, with a note on lectotypification of Spiraea hypoleuca - Pusalkar, Prashant K.; Ingle, Priyanka; Lahane, Yogesh (Phytotaxa, 2025)
Based on diagnostic character value assessment and variation range study, Spiraea duthieana (Rosaceae), a species reported after a century from Kumaun Himalaya, is proposed to be treated as a variety of Spiraea hypoleuca and hence a new combination Spiraea hypoleuca var. duthieana is proposed. A note is also appended on the lectotypification of Spiraea hypoleuca.